Identification and Characterization of Chemical Constituents in HuaTanJiangQi Capsules by UPLC-QTOF-MS Method. (23rd January 2021) - Li, Chenhui; Fang, Wei; Wu, Qingqing; Yao, Zhaomin; Wu, Jie; Huang, Peng; Wang, Dianlei; Li, Zegeng
Abstract: Background: HuaTanJiangQi (HTJQ) is a classical Chinese medicine compound preparation, mainly used for clinically treating and improving chronic obstructive pulmonary disease (COPD) in China. Objective: To establish a rapid and efficient analytical method for the identification and characterization of chemical constituents in HTJQ based on ultra-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-QTOF-MS). Method: UPLC-QTOF-MS was used to rapidly separate and identify the chemical constituents of HTJQ via a gradient elution system. The accurate mass data of the protonated and deprotonated molecules and fragment ions were detected in positive and negative ion modes. Compounds of HTJQ can be identified and assigned by analyzing accurate mass measurements and ion fragmentation mechanisms and comparing them with a chemical compositions database. Results: A total of 61 compounds in HTJQ were separated and identified, including 14 flavonoids, 16 organic acids, four isothiocyanic acids, eight butyl phthalides, two alkaloids, 10 terpenoids, four methoxyphenols and furanocoumarins, and three other compounds. The chemical compounds of HTJQ were identified and elucidated comprehensively for the first time. Conclusions: A rapid, accurate, and efficient UPLC-QTOF-MS method has been developed for the identification of chemical components and applied to simultaneously evaluate the quality and effectiveness of HTJQ. Highlights: Systematic identification of chemical constituents in HTJQ can provide a scientific and reasonable basis for the application of HTJQ in the clinical treatment of COPD.